Menanamkan Kreativitas Melalui Pembuatan Lilin Aromaterapi Dari Minyak Jelantah Untuk Komunitas Anak “Sanggar Sadar Belajar” Ploso Kuning, Sleman - Prasanti, Fransiska Tyas Virya; Riestanti, Nauryza Dwi; Rosita, Sahnas Amalia; Hidayat, Muhammad Taufik; Purwate, I Putu; Parmadi, Yosia; Sumarah, Ignatia Esti (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
Processing used cooking oil into aromatherapy candles is a community service activity carried out at Sanggar Sadar Belajar. This activity is based on the large amount of used cooking oil production in the surrounding environment, so there is a need for nature-based learning for children to be able to preserve their environment. Thus, this service activity provides an opportunity for studio children to gain new experience and knowledge in processing used cooking oil into aromatherapy candles. This service activity was carried out at Sanggar Sadar Belajar on Thursday, April 18 2024 and Sunday, April 21 2024. This activity was carried out in three stages, namely the preparation stage, implementation stage and evaluation stage. Based on the results of the pretest and posttest, this service activity can be useful in instilling creativity in studio children in processing used cooking oil into aromatherapy candles.